2000
DOI: 10.1016/s0960-9822(00)00801-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PDK-1 activity causes a reduction in cell proliferation and survival

Abstract: 3-Phosphoinositide-dependent kinase-1 (PDK-1) was identified by its ability to phosphorylate and activate protein kinase B (PKB) in vitro [1,2] and can phosphorylate and activate additional protein kinases in the AGC family in vitro [3-6]. Its role in vivo has, however, only begun to be addressed. We used antisense oligonucleotides directed against PDK-1 expression to explore the role of PDK-1 in human glioblastoma cells (U87-MG), which express a mutant PTEN allele. Reduction in PDK-1 levels resulted in inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 16 publications
(18 reference statements)
5
70
0
1
Order By: Relevance
“…Phosphorylation of Thr-308, which is dependent on PDK1, is thought to be prerequisite for Akt activation (29). Antisense PDK1 oligonucleotide has been shown to inhibit phosphorylation of both Thr-308 and Ser-473 of Akt (37). However, recent studies using PDK1Ϫ/Ϫ cells suggest that phosphorylation of Ser-473 may be independent from Thr-308 phosphorylation (38).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of Thr-308, which is dependent on PDK1, is thought to be prerequisite for Akt activation (29). Antisense PDK1 oligonucleotide has been shown to inhibit phosphorylation of both Thr-308 and Ser-473 of Akt (37). However, recent studies using PDK1Ϫ/Ϫ cells suggest that phosphorylation of Ser-473 may be independent from Thr-308 phosphorylation (38).…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that T157 of p27 Kip1 is important for nuclear localization and Cdk-2 inhibition. Furthermore, T157 is located within the nuclear localization sequence of p27 Kip1 (amino acids [151][152][153][154][155][156][157][158][159][160][161][162][163][164][165][166] and is contained in a putative Akt consensus phosphorylation site (RXXRXXT 157 D). Using breast cell lines as a model, it was shown that Akt could phosphorylate p27 Kip1 on T157 both in vitro and in vivo.…”
Section: Pi3k/akt Pathway and P27 Kip1mentioning
confidence: 99%
“…150 Similar results were obtained from studies of antisense oligonucleotides targeted to PDK1. 151 Earlier in this review, it was discussed that PI3K is a known downstream substrate of the GTPase Ras. Disruption of Ras activity may also be effective for inhibition of the PI3K/Akt pathway.…”
Section: Pi3k/akt Pathway As a Target For Chemotherapymentioning
confidence: 99%
“…7-hydroxystaurosporine (UCN-01) inhibits PDK1 nonselectively and has been reported to abrogate tumor cell growth and promote apoptosis (52,53). PDK1 antisense oligonucleotides have shown to reduce glioblastoma cell proliferation and survival (54).…”
Section: Figmentioning
confidence: 99%